The Phosphoenolpyruvate:Sugar Phosphotransferase System Is Involved in Sensitivity to the Glucosylated Bacteriocin Sublancin - Garcia De Gonzalo, C. V. (Antimicrob Agents Chemother, 2015)
The mode of action of a group of glycosylated antimicrobial peptides known as glycocins remains to be elucidated. In the current study of one glycocin, sublancin, we identified the phosphoenolpyruvate:sugar phosphotransferase system (PTS) of Bacillus species as a key player in bacterial sensitivity. Sublancin kills several Gram-positive bacteria, such as Bacillus species and Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA). Unlike other classes of bacteriocins for which the PTS is involved in their mechanism of action, we show that the addition of PTS-requiring sugars leads to increased resistance rather than increased sensitivity, suggesting that sublancin has a distinct mechanism of action. Collectively, our present mutagenesis and genomic studies demonstrate that the histidine-containing phosphocarrier protein (HPr) and domain A of enzyme II (PtsG) in particular are critical determinants for bacterial sensitivity to sublancin.